Intrafamilial and extrafamilial sexual assault and its association with alcohol consumption - Valle, Rubén; Bernabé-Ortiz, Antonio; Gálvez-Buccollini, Juan Antonio; Gutiérrez, César; Martins, Silvia S (Revista de Saúde Pública, 2018)
OBJECTIVE: Analyze the prevalence of intrafamilial and extrafamilial sexual assault in adolescents of Peru and its association with alcohol consumption. METHODS: We used a two-step and stratified probabilistic sampling to select male and female students in secondary education from all over Peru. The study included data from 54,756 students with information on demographics, alcohol and drug use, and sexual assault. The statistical analysis considered the complex sampling and we conducted two independent analyses by type of sexual assault (intrafamilial and extrafamilial), stratified by the sex of the victim. RESULTS: The prevalence of life of intrafamilial sexual assaults (5.4%, 95%CI 5.0–5.8) was similar to that of extrafamilial sexual assaults (6.1%, 95%CI 5.6–6.6). Alcohol consumption in the past year was associated with intrafamilial and extrafamilial sexual assaults that occurred in the same period after adjusting for confounders. Alcohol consumption in the past year was associated with non-physical and physical forms of intrafamilial and extrafamilial sexual assaults in the disaggregated analysis by type of assault. Alcohol consumption in the past year was associated with extrafamilial rape only among females (ORa = 2.8; 95%CI 1.3–5.9). CONCLUSIONS: Sexual assault against adolescent males and females by family members is a frequent form of victimization that is associated with alcohol consumption in Peru. It is important to examine this form of victimization among adolescents, especially those who consume alcohol.